Heavy-flavour production at forward rapidity as a function of charged-particle multiplicity with ALICE at the LHC - Mhlanga, Sibaliso (Department of Physics, 2020)
Heavy-flavour hadrons are hadrons made up of at least a charm or beauty heavy quark. They are produced in the early stages of ultra-relativistic collisions via hard scatterings and are important tools for studying different aspects of Quantum Chromodynamics (QCD) in hadronic collisions. Charged-particle multiplicity gives information on the global characteristics of the event and could be used to characterize particle production mechanisms. In hadronic collisions at Large Hadron Collider (LHC) energies, there is a significant contribution of Multiple Parton Interactions (MPI), i.e. several hard partonic interactions occurring in a single collision between nucleons. Therefore, the measurement of heavy-flavour hadrons as a function of charged-particle multiplicity gives insight into the mechanisms influencing their production in hadronic collisions at these energies and is a tool to test the influence of MPIs. Furthermore, charged-particle multiplicity dependence of heavy-flavour hadron production is used to test the ability of QCD theoretical models to reproduce data. In this thesis we investigate the production of heavy flavours via the single muon decay channel at forward rapidity as a function of the charged-particle multiplicity measured at central rapidity in proton-lead (p–Pb) collisions at √ sNN = 8.16 TeV using ALICE (A Large Ion Collider Experiment) at the LHC. ALICE is a dedicated detector optimized to study ultra-relativistic heavy-ion collisions in which the Quark-Gluon Plasma (QGP - the state of matter which prevailed in the Early Universe shortly after the Big Bang) is created. ALICE also studies proton-proton (pp) and p–Pb collisions. In pp collisions, production cross sections obtained from data provide information used to test pQCD theories while in p–Pb collisions, where the energy density is believed to be too low to produce the QGP, the presence of additional nuclear matter can alter the wavefunction of the nucleus leading to modified observables - the so-called cold nuclear matter (CNM) effects. The study of the multiplicity dependence of heavy-flavour production in p-Pb collisions may give important information regarding initial-state effects in CNM. Both pp and p– Pb collisions provide reference for comparison with heavy-ion (Pb–Pb) collisions. ALICE measures hadrons, leptons, and photons up to very high transverse momentum (pT) ≈100 GeV/c. The detector consists of a central barrel, which covers a rapidity of |y| < 1 and a Muon Spectrometer which covers the forward rapidity, -4 < y < -2.5. In this thesis, the production of heavy flavours via the contribution of their muonic decays to the inclusive pT-differential muon yield at forward (2.03 < ycms < 3.53) and backward (-4.46 < ycms < -2.96) rapidity reconstructed with the Muon Spectrometer and charged-particle multiplicity using the Silicon Pixel Detector located in the central barrel (|y| <1) in p-Pb collisions at √ sNN = 8.16 TeV in the forward and backward rapidity are studied. The aim of the study is to probe the role of MPIs in the production of heavy flavours focusing on the contribution of hard and soft processes as well as to investigate effects of the presence of multiple binary nucleon-nucleon interactions and the initial state effects modified by CNM in particle production.